Myths in psychology: psychological misconceptions among Spanish psychology students - Rodríguez-Prada, Cristina; Orgaz, Cristina; Cubillas, Carmelo P. (PeerJ, 2022)
Myths in Psychology are beliefs that are widely spread and inconsistent with the empirical evidence available within this field of knowledge. They are characterized by being relatively stable, resistant to change, and prevalent both among the non-academic population and among students and professionals within this discipline. The aim of this study was to analyse the prevalence of these myths among Spanish psychology students and the influence of three variables: the type of university, face-to-face (UAM) and online (UNED), the academic year in which participants were enrolled and familiarity with scientific dissemination. Results show that participants from the face-to-face university, enrolled in higher academic years and that reports familiarity with scientific dissemination believe less in myths than those from the online university, enrolled in lower years and that report no familiarity with scientific dissemination.
Keywords: Myths in psychology; Higher education; Scientific dissemination; Academic year